Deciphering COVID-19 Severity: Assessing FGF-18, WNT-5A, IL-17, and IL-33 Levels in the Infected Patients - Muhammed, Peshang Mohsin; Smail, Shukur Wasman; Amin, Kawa Abdulla Muhammed (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2) is a novel coronavirus that causes an infectious disease named coronavirus disease-2019 (COVID-19). Objectives: To test some biomarkers (Fibroblastic growth factor (FGF)- 18, wingless-related integration site (WNT-5A), interleukin (IL)-17, and IL-33 to predict the severity of COVID-19. Patients and Methods: A cross-sectional study was done on 180 participants (90 healthy control and 90 COVID-19-positive patients) at the emergency units of the hospitals in four cities of Northern Iraq from July 01 to December 01, 2021. The obtained serum from collected blood was tested to determine IL-17, IL-33, FGF-18, and WNT-5 levels using the ELISA technique. Additionally, CRP concentration was measured using immunoturbidimetry on Cobas c311. Results: Regarding the sociodemographic data, most moderately infected patients were aged 46- 64 years and were males (35.6%, 64.4%, respectively). The most severely infected patients were older than 65 years and were females (60%). The highest mean serum levels of C-reactive protein (CRP) (59.53±40.06 mg/dl), IL-17 (36.90±22.61 pg/ml), FGF-18 (179.8±291.37 pg/mL), IL-33 (248.11±506.71 pg/ml) were reported among the severely infected patients, while the highest mean serum level of WNT-5A was observed among moderately infected patients (5.03±5.73 ng/ml). Regarding the correlations between biomarkers, in moderately infected patients, a negative correlation between CRP and IL-33; CRP and IL-17 was observed, with a positive correlation between IL-33 and IL-17. Conversely, no correlations were seen between IL-33 and WNT-5 whereas correlations between IL-33 and IL-17 were seen in severely infected individuals. Simultaneously, a correlation between the patient’s body mass index (BMI) and CRP was detected. Conclusions: The disease was more severe among elderly, females, and overweight patients. All biomarkers, except WNT-5A, were significantly associated with the severity of COVID-19.
Keywords: COVID19 infection; pandemic disease; inflammation; biomarkers; immune system